Pengaruh Tingkat Pendidikan, Indeks Prestasi Kumulatif, Dan Gender Terhadap Dilema Etika - Abdul Hadi Asri; Efrizal Syofian; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to examine 1) The effect of education level on ethical dilemmas in accounting students at Padang State University, 2) The effect of cumulative achievement index on ethical dilemmas in accounting students at Padang State University, and 3) The influence of gender on ethical dilemmas in accounting students at Padang State University. This research is a type of causative research. This research uses a research instrument in the form of an ethical dilemma scenario with 213 respondents of accounting students. Data analysis techniques using the chi square test. The results of the study found that 1) The level of education was proven to have a significant positive effect on ethical dilemmas with the sig value of questions 1, questions 2, questions 3, and questions 4 in the ethical dilemma scenario of 0.028; 0.026; 0.003; 0.004 which is smaller than 0.05. 2) The cumulative achievement index is proven to have a significant positive effect on ethical dilemmas with a sig in question 1, question 2, question 3, and question 4 of 0.001; 0,001; 0,000; 0,000 <0.05. 3) Gender was not proven to have a significant positive effect on ethical dilemmas with the value of question 1, question 2, question 3, and question 4 in the ethical dilemma scenario of 0.234; 0.288; 0.510; 0.444> 0.05.